CCL8 and the Immune Control of Cytomegalovirus in Organ Transplant Recipients. Issue 7 (12th March 2015) - Lisboa, L. F.; Egli, A.; Fairbanks, J.; O'Shea, D.; Manuel, O.; Husain, S.; Kumar, D.; Humar, A.
<x xml:space="preserve">Abstract</x> Monitoring of cytomegalovirus cell‐mediated immunity is a promising tool for the refinement of preventative and therapeutic strategies posttransplantation. Typically, the interferon‐γ response to T cell stimulation is measured. We evaluated a broad range of cytokine and chemokines to better characterize the ex vivo host‐response to CMV peptide stimulation. In a cohort of CMV viremic organ transplant recipients, chemokine expression—specifically CCL8 (AUC 0.849 95% CI 0.721–0.978; p = 0.003) and CXCL10 (AUC 0.841, 95% CI 0.707–0.974; p = 0.004)—was associated with control of viral replication. In a second cohort of transplant recipients at high‐risk for CMV, the presence of a polymorphism in the CCL8 promoter conferred an increased risk of viral replication after discontinuation of antiviral prophylaxis (logrank hazard ratio 3.6; 95% CI 2.077–51.88). Using cell‐sorting experiments, we determined that the primary cell type producing CCL8 in response to CMV peptide stimulation was the monocyte fraction. Finally, in vitro experiments using standard immunosuppressive agents demonstrated a dose‐dependent reduction in CCL8 production. Chemokines appear to be important elements of the cell‐mediated response to CMV infection posttransplant, as here suggested for CCL8, and translation of this knowledge may allow for the tailoring and improvement of preventative strategies.